Trichodysplasia spinulosa: a polyomavirus infection specifically targeting follicular keratinocytes in immunocompromised patients. (28th January 2016) - Rouanet, J.; Aubin, F.; Gaboriaud, P.; Berthon, P.; Feltkamp, M.C.; Bessenay, L.; Touzé, A.; Nicol, J.T.J.; Franck, F.; D'Incan, M.
Summary: Trichodysplasia spinulosa (TS) is a rare skin disease, caused by a specific polyomavirus, occurring in immunocompromised patients. The pathophysiological mechanisms of TS are not yet fully understood. By using polymerase chain reaction and skin biopsy immunostaining we report evidence, in a paediatric case, of follicular keratinocytes being the primary target of trichodysplasia spinulosa‐associated polyomavirus. Abstract : What's already known about this topic? Trichodysplasia spinulosa is a rare skin disease, caused by a specific polyomavirus, occurring in immunocompromised patients. Pathophysiological mechanisms of trichodysplasia spinulosa are not yet fully understood. Cellular elements targeted by trichodysplasia spinulosa‐associated polyomavirus (TSPyV) are not documented as yet. What does this study add? Our study suggests that follicular keratinocytes are the primary target of TSPyV.